Hypophosphatemia after cardiopulmonary bypass: incidence and clinical significance, from a single centre in South Africa - Grobbelaar, Laurence Edward (University of the Free State, 2018)
Abstract not available
Dissertation (M.Med. (Anaesthesiology))--University of the Free State, 2018
Keywords: Hypophosphatemia; Cardioplegic solutions